High-risk alcohol consumption is associated with mitochondrial damage-associated molecular patterns in people living with HIV - Shannon R. Gilstrap; Micheal D. Ho; Joanna M. Hobson; Dyan M. White-Gilliam; Khalid Freij; Michael A. Owens; Shameka L. Cody; S. Justin Thomas; Robert E. Sorge; Burel R. Goodin (Drug and Alcohol Dependence Reports)
Alcohol (i.e., ethanol; EtOH) use disorders are common in people with HIV (PWH) and are associated with poor health outcomes. One potential reason for these poor health outcomes in PWH is that alcohol use is associated with mitochondrial damage and dysfunction, potentially leading to cell death. However, the link between alcohol use and mitochondrial functioning in PWH remains unclear. This study specifically investigated the relationship between high-risk alcohol consumption and mitochondrial damage-associated molecular patterns (mDAMPs) in PWH and people without HIV. We analyzed mDAMPs in 122 participants (51 HIV, 71 HIV-) before and after exposure to experimental pain testing to examine mDAMPs reactivity in response to noxious stress. Mitochondrial DAMPs were quantified from serum samples using real-time polymerase chain reaction, providing two variables: ND1 and ND6. High-risk alcohol consumption was assessed using the Alcohol Use Disorders Identification Test – C (AUDIT-C) questionnaire. In this study, we tested whether HIV status influenced the relationship between high-risk alcohol use and mitochondrial damage. Our findings revealed that PWH who engaged in high-risk alcohol consumption exhibited significantly increased mDAMPs following exposure to experimental pain testing for both ND1 (p = 0.045) and ND6 (p = 0.047). These results suggest that the effects of alcohol consumption on mitochondrial damage and dysfunction may be exacerbated by HIV infection. This study highlights the risk of high-risk alcohol consumption on mitochondrial health for PWH.